Primordial germ cells: the first cell lineage or the last cells standing? - Johnson, Andrew D.; Alberio, Ramiro (Company of Biologists, 2015)
Embryos of many animal models express germ line determinants that suppress transcription and mediate early germ line commitment, which occurs before the somatic cell lineages are established. However, not all animals segregate their germ line in this manner. The ‘last cell standing’ model describes primordial germ cell (PGC) development in axolotls, in which PGCs are maintained by an extracellular signalling niche, and germ line commitment occurs after gastrulation. Here, we propose that this ‘stochastic’ mode of PGC specification is conserved in vertebrates, including non-rodent mammals. We postulate that early germ line segregation liberates genetic regulatory networks for somatic development to evolve, and that it therefore emerged repeatedly in the animal kingdom in response to natural selection.